Under-reporting of road traffic accidents in traffic police records- a cross sectional study from North India - Singh, Preeti; Lakshmi, P. V. M; Prinja, Shankar; Khanduja, Puneet (International Journal Of Community Medicine And Public Health, 2018)
Background: Underreporting of deaths and injuries resulting from road traffic accidents is a major issue globally. Understanding the extent of underreporting and the causes along with the assessment of quality of data available will help in developing a better system of reporting and accurate estimation of burden and risk factors which aid in developing prevention programmes. Methods: A cross sectional study was done keeping hospital records as a baseline data to which the under reporting in the police records on traffic injuries was measured. The population under study was the total number of accidents that took place in Chandigarh in the month of June-July 2011 and had reported to the emergency department of three major government hospitals. These three hospitals have been selected purposefully as majority of the road traffic accident victims are being admitted/ treated in these hospitals. Results: A total of 537 cases and 375 cases were recorded in police and hospital records respectively for the month of June-July 2011. Only 15% cases from the police records were matched with the hospital records. Among the matched 64% were completely matched and 36% were partially matched cases. None of fatal injuries registered in both the records were among the matched cases. Most of the road traffic accident cases (79.4%) involved males aged 20-49 years. The official records of road accidents have been found to be incomplete in terms of number of accident and information on age, sex, address of the victim, type and severity of injury. Conclusions: A standardised reporting format of all RTIs should be developed and maintained by both the police and hospitals. All hospitals should mandatorily report all RTI cases reported to them to the police to ensure completeness.